26y+8=6y-8

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

26⋅(y-8)=(y+8)⋅6

Simplify 26⋅(y-8).

Apply the distributive property.

26y+26⋅-8=(y+8)⋅6

Multiply 26 by -8.

26y-208=(y+8)⋅6

26y-208=(y+8)⋅6

Simplify (y+8)⋅6.

Apply the distributive property.

26y-208=y⋅6+8⋅6

Simplify the expression.

Move 6 to the left of y.

26y-208=6⋅y+8⋅6

Multiply 8 by 6.

26y-208=6y+48

26y-208=6y+48

26y-208=6y+48

Move all terms containing y to the left side of the equation.

Subtract 6y from both sides of the equation.

26y-208-6y=48

Subtract 6y from 26y.

20y-208=48

20y-208=48

Move all terms not containing y to the right side of the equation.

Add 208 to both sides of the equation.

20y=48+208

Add 48 and 208.

20y=256

20y=256

Divide each term by 20 and simplify.

Divide each term in 20y=256 by 20.

20y20=25620

Cancel the common factor of 20.

Cancel the common factor.

20y20=25620

Divide y by 1.

y=25620

y=25620

Cancel the common factor of 256 and 20.

Factor 4 out of 256.

y=4(64)20

Cancel the common factors.

Factor 4 out of 20.

y=4⋅644⋅5

Cancel the common factor.

y=4⋅644⋅5

Rewrite the expression.

y=645

y=645

y=645

y=645

y=645

The result can be shown in multiple forms.

Exact Form:

y=645

Decimal Form:

y=12.8

Mixed Number Form:

y=1245

Solve for y 26/(y+8)=6/(y-8)